2009
DOI: 10.5539/ijef.v1n1p150
|View full text |Cite
|
Sign up to set email alerts
|

Board Structure and Corporate Performance in Malaysia

Abstract: This study examines the association between board structure and corporate performance, where performance is defined as the value added (VA) efficiency of the firm's physical and intellectual resources rather than the more commonly used financial terms or profitability ratios. It is argued that the inclusion of intellectual elements into the measurement provides a long-term measurement of corporate performance. The VA efficiency of the firm's total resources is calculated using the Value Added Intellectual Coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
115
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 47 publications
20
115
3
Order By: Relevance
“…By the same token, Dalton et al (1999) showed positive relationship between board size and firm performance. Abidin, Kamal and Jusoff (2009) also established similar pattern using 75 listed Malaysian firms. On the basis of the preceding literature, the hypothesis below is formulated: H2: Other things being equal, board size is significantly correlated to corporate operating performance.…”
Section: Board Sizementioning
confidence: 92%
See 1 more Smart Citation
“…By the same token, Dalton et al (1999) showed positive relationship between board size and firm performance. Abidin, Kamal and Jusoff (2009) also established similar pattern using 75 listed Malaysian firms. On the basis of the preceding literature, the hypothesis below is formulated: H2: Other things being equal, board size is significantly correlated to corporate operating performance.…”
Section: Board Sizementioning
confidence: 92%
“…Though the positive relationship between board size and operating performance indicated by regression coefficient contradict the proposition by the agency theory, the result is consistent with findings of some past studies which also reported positive relationship between the two variables. For instance, the study of Abidin et al (2009) reported that board size has positive impact on financial performance. The same result was also found in a more recent investigation by Johl, Kaur and Cooper (2015).…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Some of the reasons stated for these corporate failures are the lack of vigilant oversight functions by the board of directors, the board relinquishing control to corporate managers who pursue their own self-interests and the board being remiss in its accountability to stakeholders. As a result, various corporate governance reforms have specifically emphasized on appropriate changes to be made to the board of directors in terms of its composition, structure and ownership configuration (Abidin, Kamal and Jusoff, 2009). Therefore, the study extends and contributes to the body of research using Nigerian data to investigate the likely impact of board structure on firms' financial performance.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The financial sector consists of 29 companies (19.0%), and finally the industrial sector trade, services and investment having 41 companies (26.5%) Panel A, Table 1 (Appendix) shows the average VAIC family firm in Indonesia at 3.12 with the range between -1.53 and 6.58 with 1:49 standard deviation. Based on the average VAIC, it can be concluded that the performance of family firms in Indonesia was lower as compared to the average value of companies in Malaysia with VAIC at 5.02 as presented in the findings by Abidin et al (2009). Whereas, Ho and Williams (2003) analyzed samples in the UK and South Africa and found that the average value VAIC was 5.32 and 4.27 respectively.…”
Section: Resultsmentioning
confidence: 98%
“…VAIC is a combination of three indicators of efficiency including (1) Capital Efficiency (CEE) (2) Human Capital This approach begins with the calculation of value added as a guide efficient use of firm capital. Valueadded output is obtained, while the input is the summation of the firm expenses which consist of interest expense, depreciation expense, tax expense, minority interest, dividends paid, and retained earnings (Abidin et al, 2009). The calculation of value-added is as follows:…”
Section: Operating Variablesmentioning
confidence: 99%